Assessment of Circulating Microribonucleic Acids in Patients With Familial Mediterranean Fever - Ferhat DEMİR and Alper Han ÇEBİ and Mukaddes KALYONCU (Archives of Rheumatology, 2020)
Objectives: This study aims to evaluate the plasma expression of microribonucleic acids (miRNAs) that may be associated with the pathogenesis of familial Mediterranean fever (FMF). Patients and methods: Thirty patients with FMF (18 males, 12 females; mean age 9.1±4.7 years; range, 3 to 15.5 years) and 30 age- and sex-matched healthy children (18 males, 12 females; mean age 9.5±4.6 years; range, 4 to 16.5 years) were included in this study. The plasma levels of four candidate miRNAs (miRNA-16, miRNA-155, miRNA-204 and miRNA-451) were measured in all subjects. The plasma levels of miRNAs were analyzed with real- time polymerase chain reaction in attack and remission periods of patients and healthy controls (HCs). Results: Plasma miRNA-204 levels of FMF patients were decreased 6.5 fold in remission period compared to HCs (p<0.001). This decrease was more prominent in M694V mutation carriers. Plasma miRNA-155 levels of FMF patients were lower in remission period (p=0.03). Conclusion: Our findings showed significant alterations in the plasma expression of miRNA-155 and miRNA-204 in FMF patients compared to HCs. Our data suggest that miRNA-155 and miRNA-204 may be related to the pathogenesis of FMF. Further comprehensive and functional researches may help to clarify the role of miRNAs in FMF and elucidate the pathogenesis of the disease.